Effective strategies to manage the teacher intellectual work productivity in distance learning - Kharadze, Natalia; Giorgobiani, Maia; Melkoshvili, Tina; Dzebisauri, Lia; Pirtskhalaishvili, Dea (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The article aims to empirically determine the effective strategies to manage intellectual work (IW) productivity (IWP) in distance learning (DL), for example, university teachers in Georgia. Based on the expert assessment methods, determining indicators for assessing the level of Teacher Intellectual Work Productivity (TIWP) of three large universities in Georgia and its current level was analyzed using the method of integral assessment. Using the ANOVA method, determined the main factors influencing the TIWP at DL. We use the decision tree to systematize the factors of influence to TIWP and substantiate effective management strategies, taking into account teachers’ qualifications, age category, and competencies to ensure the continuity and quality of DL. The results allow flexibility in managing the TIWP in the DL conditions and determining the most effective management strategies, taking into account the characteristics of teachers and the current level of development of the TIWP.